Medical Image Computing and Computer Assisted Intervention - MICCAI 2021: 24th International Conference, Strasbourg, France, September 27-October 1, 2021, Proceedings, Part IV - de Bruijne, Marleen; Cattin, Philippe C; Cotin, Stéphane; Padoy, Nicolas; Speidel, Stefanie; Zheng, Yefeng; Essert, Caroline (Lecture Notes in Computer Science, 2021)
The eight-volume set LNCS 12901, 12902, 12903, 12904, 12905, 12906, 12907, and 12908 constitutes the refereed proceedings of the 24th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2021, held in Strasbourg, France, in September/October 2021.* The 531 revised full papers presented were carefully.